2011
DOI: 10.2741/204
|View full text |Cite
|
Sign up to set email alerts
|

Podocyte dysfunction in aging - related glomerulosclerosis

Abstract: We review podocyte molecular structure and function, consider the underlying mechanisms related to podocyte dysfunction and propose that podocyte dysfunction be considered in the evaluation and management of age-associated glomerulosclerosis. With aging, progressive sympathetic activation, increased intrarenal renin-angiotensin system (RAS) activity, endothelin system and oxidative stress and reduced nitric oxide (NO)-availability can damage podocytes. Apoptosis and proliferation are the principal podocyte cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 123 publications
(125 reference statements)
2
16
0
Order By: Relevance
“…[23][24][25][26][27] Several studies have indicated that loss of podocytes plays an important role in age-related glomerulosclerosis. 26,[28][29][30] It was unclear until now whether lost podocytes were at least partially regenerated and if age-related glomerulosclerosis was, thus, caused by an insufficient replacement of podocytes. 31 The aged PEC-rtTA mice showed typical changes within the glomerulus associated with kidney aging 27 (i.e., mesangial matrix expansion, thickening of the GBM with formation of spikes/humps, proteinuria, and podocyte hypertrophy).…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26][27] Several studies have indicated that loss of podocytes plays an important role in age-related glomerulosclerosis. 26,[28][29][30] It was unclear until now whether lost podocytes were at least partially regenerated and if age-related glomerulosclerosis was, thus, caused by an insufficient replacement of podocytes. 31 The aged PEC-rtTA mice showed typical changes within the glomerulus associated with kidney aging 27 (i.e., mesangial matrix expansion, thickening of the GBM with formation of spikes/humps, proteinuria, and podocyte hypertrophy).…”
Section: Discussionmentioning
confidence: 99%
“…Our data confirmed that TNF-α was a target gene of miR-130a-3p and miR-301a-3p. We also observed an inhibitory effect of si-TNF-α on HG-induced oxidative stress and apoposis in podocytes, which could increase intrarenal renin-angiotensin system (RAS) activity and reduce nitric oxide (NO) availability to trigger glomerular disease (36). Because TNF-α is involved in HG-induced podocytes dysfunction, our results suggest that miR-130a-3p or miR-301a-3p is likely to be a novel biomarker or new potent therapeutic target for podocytes injury-related renal disease.…”
Section: Discussionmentioning
confidence: 86%
“…Proteinuria is an hallmark of ORG and the podocyte is the common treath of proteinuric disease (122). Although lifestyle modification (salt restriction, hypocaloric diet and regular aerobic exercise) and angiotensin-converting enzyme inhibitors have shown benefical effects on obesity-associated proteinuria, only weight loss in early stages of the disease remains the most effective measure to definitely control proteinuria (124).…”
Section: Pharmacologic Targeting Of Podocyte Injury In Obesity-relmentioning
confidence: 99%